Swing and Electrode Diameter Effects on Toughness and Hardness of Stainless Steel 304 MIG Welding Results - Alifian, Fahrizal; Setiawan, Eko Agung; Rosidah, Afira Ainur (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Welding is one of the commonly used methods for joining metals. One of the welding techniques frequently employed is MIG welding (Metal Inert Gas welding). This type of welding is typically used for joining stainless steel. Consequently, many factors need to be analyzed to achieve optimal welding results. The objective of this research is to investigate the influence of swing variation and electrode diameter on hardness, toughness, and macrostructure from the welded stainless steel 304 using MIG welding. The research results showed the highest toughness test results with a 2.0 mm electrode diameter and a zig-zag swing of 0.459 J/mm2, while the lowest toughness test results were obtained with a 2.6 mm electrode diameter and a spiral swing of 0.201 J/mm2. The highest hardness test results were observed with a 2.6 mm electrode diameter and a zig-zag swing in the Heat Affected Zone (HAZ) at 292.0 kg/mm2, whereas the lowest hardness test results were obtained with a 2.0 mm electrode diameter and a zig-zag swing in the welded metal at 203.6 kg/mm2. The widest HAZ occurred with the spiral swing variation and a 1.5 mm electrode diameter, resulting in a HAZ width of 1.92 mm, while the narrowest HAZ of 1.25 mm occurred with the spiral swing variation and a 2.0 mm electrode. Thus, it can be concluded that the electrode diameter variation affects the results of toughness, hardness, and macrostructure tests.